PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SD NEGERI 001 JAPURA KECAMATAN LIRIK KABUPATEN INDRAGIRI HULU - Sri Nur Dewita; Otang Kurniaman; Gustimal Witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research was carried out starting from an average many IPS students' learning outcomes with a low number of students who did not complete that 12 students 60% while the category amounted to 8 students complete 40%. The purpose of this research is to improve learning outcomes IPS with the implementation of cooperative learning model of Make A Match. So we propose the following problem lies, whether the implementation of cooperative learning model of Make A Match can improve learning outcomes Elementary School third grade students 001 Japura? This research method using Action Research (PTK), the study was conducted in two cycles with each cycle two meetings and one ulagan times daily. The study involved third grade students of SD Negeri 001 Japura many as 20 students. This action was conducted from March to April 2015. The results of the data obtained from the social studies beginning with an average of 59.75 categorized less with mastery of at least 70 with KKM standards. In the first cycle UH I gained an average of 73.75 IPS learning outcomes with enough categories, and the second cycle II UH learning outcomes increased to 80.50 categorized either. Results of the study in the first cycle, the teacher during the learning process is less understood methods of cooperative Make A Match making it difficult to apply. But in the second cycle, Make A Match cooperative method can already be applied to the fullest. It is marked with the number of students who pass in this social studies. Conclusions from this research is the type of cooperative model of Make A Match been successfully applied optimally in the results of social studies class III Elementary School 001 Japura.Keywords: Cooperative Learning Model Make A Match, learning outcomes IPS.PENERAPAN